Public finance regulatory compliance among public secondary schools - Kyeyune Nakyeyune, Gorrettie; Tauringana, Venancio; Mpeera Ntayi, Joseph; Korutaro Nkundabanyanga, Stephen (International Journal of Social Economics, 2016)
The purpose of this paper is to investigate the relationship between deterrence measures, leadership support and public finance regulatory compliance among public secondary schools in Uganda. Design/methodology/approach – A questionnaire survey of 257 Ugandan public secondary schools was undertaken. Ordinary least squares regression was used to determine whether, in addition to deterrence measures, leadership support also explains variances in public finance regulatory compliance. Findings – Results based on a hierarchical regression analysis indicate that deterrence measures explain 17.4 per cent of variances in public finance regulatory compliance. In addition, leadership support explains a further 18.2 per cent of the variances in public finance regulatory compliance. Research limitations/implications – The results imply that in addition to deterrence measures, secondary schools in Uganda should also emphasise leadership support in order to improve their public finance regulatory compliance. Originality/value – Contrary to previous studies, the authors explain regulatory compliance using deterrence measures and leadership support in a single study while also focussing on institutions and not individuals as a unit of analysis. The authors also extend the predominantly financial institutions compliance studies to the education sector. Thus probably for the first time, the authors show that leadership support complements deterrence measures in explaining public finance regulatory compliance in the education sector. Even with strong deterrence measures, the lack of leadership support may lead to inadequate public finance regulatory compliance.
Keywords: Deterrence measures; Leadership support; Public finance regulatory compliance; Public secondary schools; Uganda